Development of Anti IgG Polyclonal Antibody Against Canine IgG and Their Roles in Diagnostic Purposes - Subhasis Batabyal; Satyam Singh; Barnan Chowdhury; Debottama Saha; Debaraj Bhattacharyya; Md. Habib; Shamik Polley; Swaraj Biswas; Apratim Maity; Adrija Chatterjee (International Journal of Vaccines, 2024)
IgG plays an important part in immunological studies and also in living bodies for providing secondary immune response which triggers as passive immunization against harmful pathogens in dogs. Purpose: The aim of this investigation is to separate, identify, and refine immunoglobulin G from canine serum. Methods: Ammonium sulphate precipitation was used to separate the dog's serum, which was then concentrated over night in a dialysis bag inside of a refrigerator. The protein sample's concentration was determined the following day using the Lowry method, and it was found to be 12.063 mg/ml. The investigation was then carried out using gel filtration column chromatography estimation, which produced a bell-shaped graph showing the absorbance vs the number of fractions. Next, SDS PAGE was used to determine the Rf values of the various bands. The marker graph was estimated using the molecular weight protein ladder log, and the unknown graphs were estimated using the antilog of the marker's molecular weight protein ladder marker. To conclude, a DID-TEST was conducted in which a single precipitin line of canine species' pure immunoglobulin G was seen against anti-serum produced in rabbits. Results: It was observed that there is a single line of precipitin of purified gigs of canine species were found against the anti-serum developed in the rabbit, and the immunoglobulin G was found to be immune reactive by DID-TEST and was confirmed fully by SDS PAGE. Discussion: The canine serum used in this investigation was separated using ammonium sulfate, purified using gel filtration column chromatography, and then subjected to immune-biochemical characterization. This was verified by SDS PAGE, which showed the presence of a single precipitin line of IgG by the DID test.
Keywords: DID test; Lowry method; SDS page; gel filtration column chromatography; immunoglobulin G